Kontribusi Tafsir Maqashidi Dalam Pengembangan Makna Teks Al-Quran: Telaah Ayat-Ayat Relasi Keluarga Dalam Tafsir Al –Azhar Karya Hamka - Fitriono, Eko Nani (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The Quran as the holy book of Muslims contains deep meaning in every verse that contains all aspects of life, including family relations. to be able to understand its meaning, the tafsir method is needed and one of the tafsir methods that has contributed to the development of the meaning of the Quranic verse is Tafsir Maqashidi, because this tafsir emphasizes understanding the intent and purpose contained in each verse of the Quran. The purpose of this study is to examine and investigate the contribution of maqashidi interpretation in the development of the meaning of the verse of the Quran especially in the verse that discusses family relations in tafsir al- azhar by hamka. This research uses a qualitative approach that is normative in nature. the data source used is the type of secondary data related to the research topic. The results of this study indicate that the contribution of Tafsir Maqashidi in developing the meaning of family relations verses is to provide a deeper understanding of family relationships and encourage awareness of the family values desired by Allah SWT. Through the approach of Tafsir Maqashidi, Hamka is able to relate the messages of the Quran to the context of life today and can convey important values, such as love, mutual respect, deliberation and responsibility in family relationships. Thus, the contribution of Tafsir Maqashidi in Tafsir Al-Azhar not only provides an understanding of religious knowledge, but also provides direction for creating good family relationships in accordance with Islamic teachings.